PENGARUH LABEL HALAL, HARGA, DAN LIFESTYLE TERHADAP KEPUTUSAN PEMBELIAN CHATIME DI SURABAYA - Hikmah, Jaudah Wafi; Fahrullah, (Universitas Negeri Surabaya, 2024)
Indonesia has the largest Muslim majority in the world, according to data collected by The Royal Islamic Strategic Studies Centre (RISSC). About 237.55 million people, or 86.7% of the total Indonesian population. This has become important enough to study how the people of Surabaya consume food and beverages that already have a halal label. Many manufacturers have opened a beverage industry business in Surabaya, especially in the bubble tea drinking business, one of which is the Chatime brand. The study aims to analyze the influence of halal labels, prices and lifestyle on Chatime purchase decisions in Surabaya. The study used a quantitative method with primary data sources from questionnaires distributed online to respondents who met the criteria. In sampling, use purposive samplings to get 100 respondents. Techniques in data processing use double linear regression analysis. The results of this study are known to have a positive and significant influence on the halal label, price and lifestyle on the decision to buy chatime in Surabaya. This suggests that Muslim consumers in Surabaya tend to consider aspects of halal labels, competitive prices, and compatibility with their lifestyle when choosing to buy Chatime products. This study provides managerial implications for chatime companies that can be an important reference to how customer responses to a Chatime product that has been produced can meet needs or persuade customers to make a buy decision.